Optimalisasi Problem-Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis Siswa dalam Pembelajaran Matematika : Sebuah Tinjauan Literatur - Supardi Uki Sajiman; Leni Nurlela (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to identify and synthesize previous research related to optimizing Problem-Based Learning (PBL) in improving students' critical thinking skills in mathematics learning through a systematic literature review. Data was collected from relevant scientific articles published in the last 10 years using certain keywords through databases such as Google Scholar, Scopus, and Web of Science. The results of the literature review show that the application of PBL consistently plays a role in improving students' critical thinking abilities, especially when supported by strategies such as the use of relevant contextual problems, structured feedback, and directed teacher guidance. These findings confirm the constructivist theory which states that meaningful learning occurs when students are actively involved in authentic problem solving. However, there are variations in results across educational levels and countries, indicating the importance of contextual adaptation in the implementation of PBL. In addition, the lack of comprehensive practical guidance and long-term evaluation instruments is a major obstacle. The conclusions of this research emphasize the need to develop clearer PBL implementation guidelines and more accurate evaluation instruments to measure its impact on students' critical thinking abilities, as well as the potential of PBL in improving the quality of mathematics learning that encourages critical thinking skills as an important competency in 21st century education.